Evaluation of visfatin levels in patients with hyperemesis gravidarum - Sanli, Cengiz; Fener, Harun; Ayyildiz, Hakan; Haliscelik, Mesut Ali; Kalayci, Mehmet (Taylor & Francis Ltd, 2026)
The severe end of the clinical spectrum of nausea and vomiting during pregnancy is referred to as hyperemesis gravidarum (HEG). Although its exact pathophysiology has not yet been fully elucidated, multifactorial mechanisms are known to play a role. Visfatin is a proinflammatory adipocytokine primarily secreted by visceral adipose tissue and is also produced by the placenta and amniotic membranes during pregnancy. This study aimed to investigate the association between HEG and serum visfatin levels in a prospective observational case-control study. A total of 90 pregnant women were included in the study, comprising 45 patients diagnosed with hyperemesis gravidarum and 45 healthy pregnant controls. The severity of nausea and vomiting in the HEG group was assessed using the PUQE-24 index. The two groups were compared with respect to serum visfatin levels, beta-hCG, cortisol, thyroid function tests (TSH, fT3, fT4), hemoglobin levels, age, body mass index (BMI), and the presence of ketonuria. Serum visfatin levels were significantly higher in the HEG group compared to controls (30.24 (23.1-56.0) & micro;g/L vs 22.2 (18.2-48.2) & micro;g/L, p = 0.04). Similarly, beta-hCG (122350 (94207-188806) IU/L vs 88866 (59112-128434) IU/L, p = 0.001) and cortisol levels (293.2 (240.1-430.5) nmol/L vs 257.5 (213.4-325.1) nmol/L, p = 0.025) were significantly elevated in the HEG group. Ketonuria, a marker of metabolic stress and fasting, was significantly more frequent in the HEG group (33/45 vs 1/45, p < 0.001). No significant differences were observed between the groups in terms of age, BMI, gestational age, or thyroid function tests (p > 0.05). Within the HEG group, visfatin levels were significantly higher in patients with severe PUQE-24 scores compared to those with mild-to-moderate scores (47.8 +/- 35 & micro;g/L vs 24.6 +/- 9.8 & micro;g/L, p = 0.032). These findings suggest that increased visfatin levels are associated with the presence and severity of HEG. Further prospective and longitudinal studies are needed to better understand this relationship.
Keywords: Hyperemesis Gravidarum; Visfatin; Adipokines; Biomarkers; Ketonuria